Exploring Indian educators' perceptions, attitudes, and behaviors regarding augmented reality applications in school settings: a comprehensive mixed-methods study - Bhattacharya, Shinjini; Sau, Arnab; Bera, Priyanka; Sardar, Chandan; Chaudhuri, Sumita; Thakur, Nabin (Frontiers in Education, 2025)
This study examined Indian school educators' perceptions, attitudes, and behaviors toward augmented reality applications (ARA), focusing on their interrelationships and the factors influencing these variables at the school level. Employing a descriptive mixed-methods approach, data were randomly collected from 730 teachers across all 28 states and 8 union territories of India using standardized, self-developed questionnaires. Quantitative analysis included percentages, chi-square, t-tests, ANOVA, multiple correlations, and coding techniques. The findings revealed that teachers exhibited low to moderate levels of perception, attitude, and behavior toward ARAs, with female teachers scoring significantly higher than their male counterparts. Notable differences were observed across school category, stream, qualification, and designation, though attitudes showed no significant variation. In contrast, age, location, and teaching experience had little to no impact. Strong positive correlations were identified among the three variables—perception and attitude, perception and behavior, and attitude and behavior—underscoring their interdependence. Qualitative insights further highlighted key barriers, including limited awareness, low motivation, inadequate infrastructure, and insufficient training. Despite these challenges, teachers demonstrated resilience by adopting adaptive strategies. The study suggests that effective integration of AR in schools requires robust administrative support, adequate funding, targeted professional development, collaborative practices, and the development of culturally relevant, discipline-specific content.